Down-regulation of ANAPC13 and CLTCL1: Early Events in the Progression of Preinvasive Ductal Carcinoma of the Breast - Sens-Abuázar, Carolina (Neoplasia Press Inc., 2012)
Alterations in the gene expression profile in epithelial cells during breast ductal carcinoma (DC) progression have been shown to occur mainly between pure ductal carcinoma in situ (DCIS) to the in situ component of a lesion with coexisting invasive ductal carcinoma (DCIS-IDC) implying that the molecular program for invasion is already established in the preinvasive lesion. For assessing early molecular alterations in epithelial cells that trigger tumorigenesis and testing them as prognostic markers for breast ductal carcinoma progression, we analyzed, by reverse transcription-quantitative polymerase chain reaction, eight genes previously identified as differentially expressed between epithelial tumor cells populations captured from preinvasive lesions with distinct malignant potential, pure DCIS and the in situ component of DCIS-IDC. ANAPC13 and CLTCL1 down-regulation revealed to be early events of DC progression that anticipated the invasiveness manifestation. Further down-regulation of ANAPC13 also occurred after invasion appearance and the presence of the protein in invasive tumor samples was associated with higher rates of overall and disease-free survival in breast cancer patients. Furthermore, tumors with low levels of ANAPC13 displayed increased copy number alterations, with significant gains at 1q (1q23.1–1q32.1), 8q, and 17q (17q24.2), regions that display common imbalances in breast tumors, suggesting that down-regulation of ANAPC13 contributes to genomic instability in this disease.